Sequential and Timely Combination of a Cancer Nanovaccine with Immune Checkpoint Blockade Effectively Inhibits Tumor Growth and Relapse. Issue 34 (6th July 2020) - Kim, Yujin; Kang, Sukmo; Shin, Hocheol; Kim, Taewoo; Yu, Byeongjun; Kim, Jinjoo; Yoo, Dohyun; Jon, Sangyong
Abstract: We describe a small lipid nanoparticle (SLNP)‐based nanovaccine platform and a new combination treatment regimen. Tumor antigen‐displaying, CpG adjuvant‐embedded SLNPs (OVAPEP ‐SLNP@CpG) were prepared from biocompatible phospholipids and a cationic cholesterol derivative. The resulting nanovaccine showed highly potent antitumor efficacy in both prophylactic and therapeutic E.G7 tumor models. However, this vaccine induced T cell exhaustion by elevating PD‐L1 expression, leading to tumor recurrence. Thus, the nanovaccine was combined with simultaneous anti‐PD‐1 antibody treatment, but the therapeutic efficacy of this regimen was comparable to that of the nanovaccine alone. Finally, mice that showed a good therapeutic response after the first cycle of immunization with the nanovaccine underwent a second cycle together with anti‐PD‐1 therapy, resulting in suppression of tumor relapse. This suggests that the antitumor efficacy of combinations of nanovaccines with immune checkpoint blockade therapy is dependent on treatment sequence and the timing of each modality. Abstract : Timing is everything : A cancer nanovaccine composed of nontoxic, biocompatible lipid components that shows highly potent antitumor efficacy was developed. In addition, the feasibility of a new combination immunotherapy regimen with a defined sequence and timing of nanovaccines and immune checkpoint blocking antibodies that effectively inhibits tumor relapse was demonstrated.